THE SIX THINKING HATS SEBAGAI UPAYA PENINGKATAN PEMBELAJARAN IPA YANG PAKEM - Purwanti Widhy (MAJALAH ILMIAH PEMBELAJARAN, 2010)
This study aims to explore how learning science with using techniques of The Six Thinking Hats to appear student activity, student creativity and creating a fun learning so the learning will be effective is to achieve the objectives learning. Basically, the discussion is focused on learning science base PAKEM using The Six Thinking Hats technique that can enable students and raise student creativity and improve students' critical thinking skills. Impacts arising from PAKEM against activity and creativity of students tested .. This study also explains how criteria of learning by using PAKEM approach and explain how the application of the Thinking Hats technique in science learning